Pengaruh Penggunaan Fintech Payment Dan Self Control Terhadap Perilaku Keuangan Konsumtif Gen Z Di Kecamatan Tamalanrea - Desvilla Bumbungan; Manuel August Todingbua; Benyamin Mongan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to analyze the influence of fintech payment usage and self-control on the consumptive financial behavior of Generation Z in the Tamalanrea District, Makassar City. The research employed a quantitative method, with primary data collected through online questionnaires distributed to 100 Generation Z respondents selected using the Slovin formula, all of whom use fintech payment services. Data were analyzed using multiple linear regression with SPSS to test both the partial and simultaneous effects of the independent variables on the dependent variable. The results reveal that, simultaneously, fintech payment usage and self-control have a significant impact on consumptive behavior. However, partially, only self-control shows a negative and significant effect, while fintech payment does not significantly affect consumptive behavior. This indicates that an individual’s ability to exercise self-control plays a more dominant role in regulating consumption behavior compared to the convenience and promotional offers provided by fintech payment platforms. The novelty of this study lies in its focus on Generation Z in urban areas with high digital penetration and active fintech payment usage, emphasizing self-control as a key factor in minimizing consumptive behavior triggered by advancements in financial technology. These findings can serve as the basis for educational recommendations on digital financial management and policies that encourage self-control in fintech usage among Generation Z.